A model of labeling with horizontal differentiation and cost variability - Saak, Alexander E. (International Food Policy Research Institute, 2011)
We study optimal disclosure of variety by a multi-product firm with random costs. In our model there are two varieties that are horizontally differentiated and differ in overall quality, but buyers cannot distinguish between them without labels. The equilibrium prices for labeled varieties are increasing functions of the absolute value of the cost differential and do not reveal which variety is cheaper to produce. Nondisclosure is most common when there is moderate uncertainty about the relative input cost, not too much idiosyncrasy in consumer valuations, and not too much difference in quality across varieties. Although mandatory disclosure of variety benefits consumers, it decreases expected welfare when relative input cost variability is large and quality asymmetry is small. The cheaper variety tends to be oversupplied (undersupplied) when disclosure is voluntary (mandatory). Competition among multi-product firms that source inputs in the same upstream market may not lead to more disclosure.”